(untitled) (Bangladesh Journal of Botany, 2019)
The micromorphological and anatomical investigations on 6 taxa of Conringia Heist. ex Fabr. growing in Turkey were carried out. The anatomy of root, stem and leaves was examined in detail. In micromorphological studies stem and leaf surface of species was examined. Mesophyll type of lamina is dorsiventral (Conringia planisiliqua, C. persica, C. austriaca) and equifacial (C. clavata, C.grandiflora, C. orientalis). Stomata situated on both surfaces, are anisocytic and rarely anomocytic types. Crystals of calcium oxalate observed in only one species (C. grandiflora) was found to have cubic type parenchyma cells of the stem and leaf. In micromorphological studies the surface of the stem and leaves were found to be glabrous. Epidermal surface of leaves was observed to be covered with waxy cuticular particles. Anticlinal walls of the adaxial cells are undulate and rarely straight and anticlinal walls of abaxial epidermis are undulate and rarely sinuate. Periclinal walls were found to be covered with upper waxy layer which was flat. A diagnostic key based on combined stem, leaf and leaf epidermal characteristics are presented. The leaf mesophyll structures, stem vascular bundles number, lignified or unlignified of sclerenchyma, epidermal surface and absence or presence of crystals were found to be important characters for the identification of Conringia species.